Myrthue-graven. Ældre romertids jordfæstegrave i sydvestjylland - Lomborg, Ebbe (Kuml, 1964)
The Myrthue grave-an Early Roman Period inhumation in southwest Jutland In the vicinity of the Early Roman Iron-Age settlement at Myrthue, which was excavated by Esbjerg Museum and is described earlier in this issue, an inhumation burial was found in April 1962 which perhaps belongs to the settlement. It lay about 80 yards north of the excavated buildings, approximately midway between the site and the bank of the Varde river where it runs into Ho Bay (cf. p. 27, Fig. 12). The grave, dug into a low natural hillock, was about 2.8 meters long E-W, about 1.6 meters wide and 80 cms. deep. The sides were very close to vertical and the bottom almost flat. Scattered through the fill, from about 20 cms. under the top of the subsoil to about 7 cms. above the bottom of the grave, there were found at nine points fragments of objects (Fig. 1), consisting of two unrecognisable fragments of iron and the sherds of two pottery vessels. The dimensions of the grave and the objects found show that we have here an inhumation from the Early Roman lron Age. However, the condition of the objects found, lying broken and scattered in the fill above the bottom of the grave, suggests that the burial had been previously disturbed and perhaps robbed. The very mottled fill, and the circumstance that only the stones along the west and south sides of the excavation for the grave lay in a perceivable order (Fig. 2), would also be explained by this hypothesis. The objects found and their date Both the handled vessel and the dish (Fig. 3) are of typical Early Roman Period shapes, of general occurrence in south Jutland. The expanded, sharply facetted rims seem to show that the grave belongs to the earlier part of the period (1st century A.D.) (2). The iron fragments are indeterminable, but may be pieces of a knife. A comparison of the pottery from the grave with the pottery found in or near the excavated house sites in the settlement reveals quite close parallels to the handled vessel from the grave (cf. above p. 26, Fig. 11). It is therefore probable, though of course not certain, that the grave and the settlement belong to each other. No other graves were found during the investigation, but as cultivation did not permit the stripping of the topsoil from a larger area it cannot be determined with certainty whether we have here an isolated grave or part of a cemetery. Parallels to the grave type In the Early Roman Iron Age inhumation graves and cremation graves are both found often in the same cemetery. Inhumation graves, however, are not equally common over the whole country, and they are of different forms in different areas. While they are the normal form of grave in north and central Jutland, the custom of cremation burial predominates in south Jutland and in Slesvig north of the border. The Myrthue grave is, however, not so isolated in southwest Jutland as one would imagine on a basis of the published discoveries. In this connection it is specially interesting that there is a little group of inhumation graves in the area of southwest Jutland between Esbjerg and the Varde river, to which the Myrthue grave belongs both geographically and typologically. As none of these graves has been described before brief details are given here. The objects discovered in these graves are all preserved at the National Museum. AIslev town and parish, Skads herred. Excavated by H. Kjær 1930. In a ploughed-down tumulus the remains of a stone enclosure were found, measuring 3.4 meters E-W and 2.3 meters N-S. It was formed of stones up to two feet in height and seems to have marked out the inhumation grave below (Fig. 4). The outlines of the grave could only be seen after the soil of the tumulus had been dug away to a depth of I meter. The grave measured 2.75 meters E-W and 1.25 meters N-S at the top, and 2.25 by 0.9 meters at the bottom. The fill contained practically no stones, but at the bottom, at each end of the grave, lay a few stones, presumably to support the coffin, and under this lay a stone cobbling. Traces of the coffin appeared at a depth of about 1.7 meters in the form of dark stripes about 5 cms. broad. The ends stood vertical, while the sides were sloping with the broadest outlines at the top, showing clearly that the planks had been pressed outwards by the weight of the earth above. Traces of the wooden bottom were also found. The skeleton was very badly preserved, but the body appears to have lain outstretched on its back with its head to the west. In the centre of the grave a gold ring was found (Figs. 4: 1; 6 : 3), and at the eastern end stood a group of pottery, consisting of a pedestal beaker (Figs. 4: 2; 5: 5), a small handled vessel (Figs. 4: 3; 5: 2) and a vase with a cylindrical neck (Figs. 4 : 4; 5 : 3). South of this group stood another pedestal beaker (Figs. 4: 5; 5 : 4), and beside it a pair of shears (Figs. 4: 6; 6: 1), a single-edged knife (Fig. 4 : 7) and a razor (Figs. 4 : 8; 6 : 2). At the west end of the grave stood a large handled vessel (Figs. 4: 9; 5: 1), while on examination of the objects discovered the present author found at the National Museum among the skeletal remains an iron fibula which had not previously been noticed (Fig. 5 : 6). The fibula (5) and the sharply facetted pottery (2) date the grave to the earlier part of the Early Roman Iron Age. Tulsmark, Alslev parish, Skads herred. Excavated 1933 by Therkel Mathiassen. On a low hillock the owner of the area had found, while moving soil, a stone layer, and on the western end of this two bronze fibulae (Fig. 8 : 4-5 and Fig. 9) and the remains of an iron fibula. Investigation revealed a grave framed by stones of about football size (Fig. 7). It measured 2.75 meters E-W by 1.5 meters. Within the stone frame were found remains of the wooden coffin in the shape of dark stripes forming an oblong 2.25 meters long and up to 0.76 meters broad. The grave was floored with a paving of flat stones laid on the subsoil sand. The grave furnishings lay on or near the paving: at the east end of the grave were a bowl (Figs. 7 : 1; 8 : 1), fragments of two iron knives (Fig. 7: 3) and a pottery vessel in fragments (Figs. 7 : 4; 8 : 2). In the centre of the grave lay a gold ring (Figs. 7: 5; 8 : 3), and in the western end a little above the bottom of the grave a piece of one of the bronze fibulae (Fig. 7 : 2). No trace was found of the skeleton. The fibulae date the grave to the earlier part of the Early Roman Iron Age (6). Forum, Brøndum parish, Skads herred. Excavated by Sigurd Schultz 1916. In a ploughed-up tumulus on sloping ground a disturbed inhumation grave was found. It was a secondary interment, oriented E-W, containing many stones but none in their original place. From among the stones sherds of four pottery vessels were recovered, most being found at the east end of the grave at the bottom. A fragment of a bronze fibula (Fig. 10) was also found in this area. Frøkær (Damsmark), Guldager parish, Skads herred. Excavated by Th. Thomsen 1913. A disturbed inhumation grave, lying E-W, was found as a secondary interment in a ploughed-up Stone-Age tumulus. The grave appeared immediately under the surface of the tumulus as an irregular heap of stones, below which the stone-filled grave-pit emerged, with an E-W length of 3.3 meters, a width of 1.5 meters and a depth of about one meter. A bowl (Fig. 11 a : 2) was found high up in the northwest corner of the stone heap, and a sherd of the same bowl in the same area about 20 cms. deeper. At the east end of the grave, and lying still deeper but not at the bottom, were sherds belonging to the pedestal bowl below. And a little deeper traces of the south side of the coffin were observed. In the bottom level there lay to the southwest a rusted lump of iron, which proved to comprise a one-edged knife, a razor and an ornamental knife (Fig. 11). In the northeastern part of the grave, also in the bottom layer, lay two incomplete vessels, to the east a pedestal bowl (Fig. 11 a: 1) and west of it a dish (Fig. 11 a: 3). No remains of the skeleton survived. The less taut facetting and outline of the pottery would suggest that the grave belongs to the later part of the Early Roman Iron Age (2). Sædding, Guldager parish, Skads herred. Contents removed by non-professional 1960. Information supplied by the finder supplemented by Niels Thomsen of Esbjerg Museum, who saw the grave after it had been emptied. The information supplied by the finder is somewhat vague. However, with the support of the later report from Esbjerg Museum and of press photographs it is possible to establish with certainty that the object was a stone-filled inhumation grave with the measurements and orientation given below. In addition, the type and composition of the objects found and their dating give no reason to doubt that they belong to one single burial. The various sources of information can be summarized as follows: Under the level field surface the grave, filled with stones and lying E-W, was about 2 meters long, one meter wide and one meter deep. It had been partially disturbed during the last war. At the bottom of the grave, in the western end, remains of wood and an iron fibula (Fig. 13 : 5) were found. A little to the east of the centre of the grave stood two pottery vessels -according to the finder inverted and the one within the other (Fig. 12: 1-2). Close by lay a lump consisting of a pair of shears (Fig. 13 : 4), a one-edged knife (Fig. 13 : 1) and a razor (Fig. 13 : 6). Under these, and pressed into the grave bottom, lay a gold ring (Fig. 13 : 2). Finally a whetstone of slate (Fig. 13 : 3) was found lying loose in the fill. According to information from Niels Thomsen there is an Early Roman Iron-Age settlement with house sites and pottery close to the grave, the relative positions of the grave and the settlement corresponding to the situation at Myrthue. The grave is dated by means of the fibula to the earlier part of the Early Roman Iron Age (6). This group of graves appears to belong to both the earlier and the later part of the Early Roman Iron Age. In every case they appear to be isolated graves, but as more extensive areas were in no case stripped around the graves the possibility cannot be excluded that one or more of them lay in fact in a cemetery. These inhumation graves are all oriented E-W, and from those that were undisturbed -and two of the disturbed graves- it appears that a group of pottery vessels was normally placed in the eastern end of the grave; at Alslev there was in addition a vessel in the western end. A knife and a razor and other iron objects were in several cases placed beside the pottery group, but in two cases similar discoveries were made in the western end. To judge by the skeletal remains at Alslev and the placing of the fibulae at Alslev, Tulsmark, and Sædding the body lay with its head to the west. In several cases remains of plank coffins were found, and the graves are all comparatively narrow. On the other hand their depth under the surface shows considerable variations, as does the use of stones. Three of the graves are laid under the natural surface (Myrthue, Tulsmark and Sædding), all lying in natural hillocks. Of the three tumulus graves two are merely secondary interments in older tumuli, and it is perhaps a matter of definition whether they should be regarded as tumulus graves. It may have been purely by chance that they are sited in artificial mounds rather than in natural mounds like the first three. Only the Alslev grave appears to have been covered by a mound, in addition to being marked out with larger stones above the surface. The report is, however, not very detailed and somewhat vague on this point. The group may appear to lie somewhat isolated in southwest Jutland, but in fact at least two other discoveries of the same type are known from this region (7-8). A comparison of the southwest-Jutland inhumations with those of mid-Jutland shows that the soutbwestern group of narrow coffin-graves with pottery placed at the eastern end of the grave are clearly distinct from the broad east-Jutland graves, where the set of pottery vessels is arranged on the south side of the grave in front of the body. There are also distinct differences in the pottery between the two areas. On the other band the narrow plank coffins are met with in western mid-Jutland and in the region north of the German border. When Brøndsted (4) particularly emphasises the coffin lying N-S as characteristic of the southernmost area of Jutland he is only partially correct. This form of grave appears in fact to be limited to the western part of this region, occurring in cemeteries in Tønder county (Il) and the western part of Haderslev county (12), while the graves further to the east lie E-W. The boundary between the N-S graves of the southernmost Jutland and the E-W graves of southwest Jutland appears to lie somewhere between Ribe and Esbjerg. The closest parallels to the Early Roman Iron-Age inhumation graves of southwest Jutland thus appeared to lie in Ringkøbing county (west central Jutland) and in the extreme southeast of Jutland. The graves of neither of these areas, however, have been sufficiently well published for a clear picture to emerge of their characters. It is thus not at the moment possible to determine whether the southwest-Jutland inhumations should be regarded as a distinct local group, or merely as outliers from one or other of the two areas named. Pending the thorough investigation of the discoveries from west and southernmost Jutland we must content ourselves with having shown that the inhumation burials of southwest Jutland are not particularly rare, and that all those discovered to date represent one specific type: the narrow, east-west-oriented grave, with the pottery placed at one end of the grave. Ebbe Lomborg